An l=2 torsatron with centered planar magnetic axis - Kotenko, V.G. (Вопросы атомной науки и техники, 2008)
The paper is concerned with properties of magnetic surface configurations that have the planar magnetic axis coincident with the circular geometrical axis of the torus. The calculations were performed for the model of an l=2 torsatron comprising additional toroidal magnetic field coils. The magnetic surfaces with a negative shear and a high magnetic well can be realized in the system. Изучаются численным методом свойства конфигураций магнитных поверхностей, которые имеют плоскую магнитную ось, совмещенную с круговой геометрической осью тора. Расчеты проводились для модели двухзаходного торсатрона с катушками дополнительного тороидального магнитного поля. В системе могут быть реализованы магнитные поверхности с отрицательным широм и большой магнитной ямой. Вивчаються чисельним методом властивості конфігурацій магнітних поверхонь, які мають плоску магнітну вісь зуміщену з круговою геометричною віссю тора. Розрахунки проводились для моделі двозаходного торсатрону з катушками додаткового тороїдального магнітного поля. В системі можуть бути зреалізовані магнітні поверхні з від’ємним широм та великою магнітною ямою